Introduction to wireless localization : with iPhone SDK examples - Chan, Eddie C. L.; Baciu, George, 1961-; IEEE Xplore (Online Service); John Wiley & Sons (Hoboken, New Jersey : Wiley, 2012)
This book provides a comprehensive overview of the entire landscape of both outdoor and indoor wireless positioning, and guides the reader step by step in the implementation of wireless positioning applications on the iPhone. Explanations of fundamental positioning techniques are given throughout the text, along with many programming examples, providing the reader with an independent, practical, and enjoyable learning of the material while gaining a real feel for the subject. . Provides an accessible introduction to positioning technologies such as Global Positioning System and Wi-Fi positioning. Presents hands-on skills to iOS 5.0 programming for location-aware applications. Gives a thorough grounding in signal propagation, line-of-sight and interference effects for accurate positioning. Covers the location-aware video streaming and conferencing with practical iPhone application examples. Accompanied by a website containing programming code described in the text and lecture presentation slides for instructors This book is primarily intended for anyone who wants to study wireless localization. It is an ideal textbook for graduate students who are first learning localization techniques, as well as advanced undergraduates in computer science interested in translating localization concepts into real code. Professionals, engineers and researchers working in location-aware services and related techniques using mobile positioning and AI technologies will find this book to be a helpful reference.Companion website for the book:www.wiley.com/go/chan/wireless.
Front Matter -- Supplemental Images -- Introduction to Wireless Localization -- Wi-Fi Positioning Systems. Installation of Wi-Fi Infrastructure -- Algorithms Used in Wi-Fi Positioning Systems -- Implementation of Wi-Fi Positioning in iPhone -- Positioning across Different Mobile Platform -- Wi-Fi Signal Visualization -- Outdoor Positioning Systems. Introduction of Global Positioning System -- Study of GPS Signal and Algorithms -- Differential GPS and Assisted GPS -- Other Existing Positioning Systems -- Applications in Wireless Localization. AI for Location-Aware Applications -- Beyond Positioning: Video Streaming and Conferencing -- Appendix A: Starting the iOS SDK -- Appendix B: Introduction to Objective-C Programming in iPhone -- Index.
In Wiley online library
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: iPhone (Smartphone) -- Programming; Location-based services; Electronic books